The inequality (or the growth) we measure. Data gaps and the distribution of incomes - Gonzalez Alvaredo, Facundo (2022)
Large gaps exist between income estimates from inequality studies and macroeconomic statistics,questioning our representation of flows and the relevance of economic growth. We take stock ofthese gaps by confronting multiple datasets in Latin America, finding that surveys account foraround half of macroeconomic income over the past twenty years. Less than half of this gap is dueto conceptual differences, the remainder coming from growing measurement issues, which mainlyconcern capital incomes. Top tails in administrative data and surveys present diverging averages,especially for non-wage incomes, and different shapes. We discuss implications for both inequalitylevels and trends.